2021
DOI: 10.1016/j.psj.2021.101361
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: A sip of stress. Effects of corticosterone supplementation in drinking water on feather corticosterone concentrations in layer pullets

Abstract: The measurement of feather corticosterone concentrations ( fCORT ) is a comparatively new method for the evaluation of stress in wild and captive birds and may be a useful indicator in animal welfare research. The aim of this study was to assess the suitability of fCORT as an indicator of stress, and for this purpose a prolonged stress period was experimentally simulated by oral intake of corticosterone via drinking water and corticosterone concentrations were analyzed in feathers grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Research has shown that CORT deposition in feathers can provide a representation of stress during feather growth in birds (Bortolotti et al, 2008;Jenni-Eiermann et al, 2015) and that exposing layer hens to CORT through drinking water, increases CORT as measured in feathers (Bartels et al, 2021). High stocking density during rearing also increased CORT levels measured in feathers in layer hen pullets (von Eugen et al, 2019).…”
Section: Feather Corticosterone Faecal Corticosterone Metabolites And...mentioning
confidence: 99%
“…Research has shown that CORT deposition in feathers can provide a representation of stress during feather growth in birds (Bortolotti et al, 2008;Jenni-Eiermann et al, 2015) and that exposing layer hens to CORT through drinking water, increases CORT as measured in feathers (Bartels et al, 2021). High stocking density during rearing also increased CORT levels measured in feathers in layer hen pullets (von Eugen et al, 2019).…”
Section: Feather Corticosterone Faecal Corticosterone Metabolites And...mentioning
confidence: 99%
“…Glucocorticoids in the blood and heterophil to lymphocyte ratio ( HLR ) are considered to be the most commonly measured biomarkers of HS in poultry due to their reliability. Glucocorticoids can be measured in the blood, feces, egg, and feather ( Weimer et al, 2018 ; Bartels et al, 2021 ; Kim et al, 2021 ; Lee et al, 2022 ; Oluwagbenga et al, 2022 , 2023b ). Although measurement of cortisol as biomarker of stress has been ignored for over 2 decades, recent studies reported an increase in circulating cortisol following exposure to HS or ACTH in poultry thereby showing its importance as an index of stress ( Sohail et al, 2010 ; Kim et al, 2022b ; Mirsaiidi Farahani and Hosseinian, 2022 ; Oluwagbenga et al, 2022 ; Tetel et al, 2022a , b ).…”
Section: Introductionmentioning
confidence: 99%